2009
DOI: 10.4321/s1130-01082009000300006
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine tumors: fascination and infrequency

Abstract: In this article, I review and update of gastro-entero-pancreatic neuroendocrine tumors, which so much fascination have risen among healthcare providers on grounds of their infrequency, hormonal syndromes, and high survival rate, is performed based on references from the past fifteen years. DEFINITIONNeuroendocrine tumors (NETs) or gastroenteropancreatic endocrine tumors (GEPETs) (2% of all gastrointestinal tumors) have their origin in tissues derived from the neural crest, neuroectoderm, and endoderm; 60-70% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Neuroendocrine tumours, particularly those of the gastro-intestinal tract, frequently express high levels of somatostatin receptors; therefore, radioisotope imaging techniques with somatostatin analogues labelled with 111 In or 99m Tc proved to be considerably more sensitive (60-90% depending on the tumour type) in visualization of lesions [3,[11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Neuroendocrine tumours, particularly those of the gastro-intestinal tract, frequently express high levels of somatostatin receptors; therefore, radioisotope imaging techniques with somatostatin analogues labelled with 111 In or 99m Tc proved to be considerably more sensitive (60-90% depending on the tumour type) in visualization of lesions [3,[11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…However, this can only be performed in 20 % of these patients (3). In our case, despite the large size of the liver metastasis and its increased aggressivity compared to the primary tumor, a full resection of the tumor was achieved, with a 5-year survival estimated higher than 60-80 % (4,5).…”
Section: Dear Editormentioning
confidence: 66%
“…Earlier studies suggested that sensitivity might increase to 100% in cystic pNETs [20,24,25] if LBC and immunocytochemistry are employed. However, these were small studies (n=9) and more recent literature suggests a diagnostic yield varying between 60% and 70%.…”
Section: Discussionmentioning
confidence: 99%
“…24 No 1: 69-75 4 year and 2 month periods, to investigate the comparative performance between solid and cystic pNETs and to assess the value of EUS and EUS-FNA in individuals with a pancreatic mass not diagnosed as a pNET after cross-sectional imaging.…”
Section: Introductionmentioning
confidence: 99%